The Space of the Family: Emotions, Economy and Materiality in Homeownership. Issue 1 (2nd January 2016) - Jørgensen, Cecilie Juul
Abstract: The role of emotions in housing markets has come under scrutiny in the housing market bubble and subsequent dramatic decline from which markets are still recovering. Thus, the performativity of housing markets has become an object for sociological analysis. Using qualitative interview data from 11 Danish first-time home-buying families, this article investigates the relations between emotions and economic behaviour in a market that has become unpredictable because of volatile price developments since the early 2000s. Identifying the relationship between economic behaviour, emotions and the materialities of homes, the article finds that home-buying is intermeshed with emotional attempts at creating or stabilizing the family as a unit. Homeownership therefore is an emotional investment through financial and material means in the future of the family, and the article therefore argues that markets are saturated with love, desire, fear, anxiety and hope.